Earnings mobility in times of growth and decline: Argentina from 1996 to 2003 - Gary S. Fields; María Laura Sánchez Puerta (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
In recent years, the economy of Argentina has experienced both rapid economic growth and severe economic decline. In this paper, we use a series of one-year long panels to study who gained the most in pesos when the economy grew and who lost the most in pesos when the economy contracted. To answer these questions, we test two hypotheses both unconditionally and conditionally. The `divergence of earnings' hypothesis holds that in any given year, the highest earning individuals are those who experienced the largest earnings gains or the smallest earnings losses in pesos. The `symmetry of gains and losses' hypothesis holds that those groups that gained the most in pesos when the economy grew are those that lost the most in pesos when the economy contracted. Both hypotheses are decisively rejected in the data. – finance ; growth ; inequality ; Argentina ; survey ; gains ; losses
Keywords: O16; D14; I31; D63; 330; Wirtschaftswachstum; Einkommensverteilung; Argentinien